Weaving a Web of ideas. - Cherry, S.M.
Engines that search for meaning rather than words will make the Web more manageable. Committees of researchers from around the globe want to make the Web more homogeneous, more data-like, more amenable to computer understanding-and then agents won't have to be so bright. In other words, if Web pages could contain their own semantics-if we had a Semantic Web-software agents wouldn't need to know the meanings behind the words.
Keywords: Semantic Web; Meaning; Search engines; Software agents